PENGARUH HORMON TIROKSIN (T4) TERHADAP KELULUSHIDUPAN DAN PERTUMBUHAN BENIH IKAN JAMBAL SIAM (Pangasius hypophthalmus) - Jarod Setiaji; T Iskandar Johan (DINAMIKA PERTANIAN, 2012)
This study aimed to investigate the effect of the hormone thyroxine (T4) on the survival and growth of fish seed jambal conjoined. The method used was experiment with completely randomized design with one factor and four treatments. The observed parameters were the absolute weight growth of fish seed jambal, the total length growth, the growth rate of daily weight percentage, and survial rate. The treatment consisted of P1 (without the hormone thyroxine), P2 (soaking with hormone thyroxine at a dose 0.2 mg / 2 liter), P3 (soaking with hormone thyroxine at a dose of 0.6 mg / 2 liter), P4 (soaking with hormone thyroxine at a dose of 1.0 mg / 2 liter). The observation results showed that the best dosage was found on soaking treatment with hormone thyroxine 1.0 mg/2 liter. On that treatment, the growth of the absolute weight of jambal siam fish seed reached 7.04 g, the absolute length growth of 3.07 cm, the growth rate of daily weight percentage of 15.91% and survival rate of 100%.